Monitoring of Cylindrical Plunge Grinding Process by Electromechanical Impedance - Ferreira, Fabio Isaac [UNESP]; De Aguiar, Paulo Roberto [UNESP]; Silva, Rosemar Batista Da; Jackson, Mark James; Baptista, Fabricio Guimaraes [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
One of the most promising monitoring techniques is based on electromechanical impedance (EMI) transducers, which are low-cost components and allow easy implementation. EMI signal features showed good results for some applications in previous studies, but it is still unexplored for machining processes, which is essential for metal-cutting industries. This paper presents a new approach to verify the applicability of EMI measurements to monitor surface quality after the plunge cylindrical grinding of non-flat parts, which require low roughness and tight dimensional tolerances. Tests were carried out in a camshaft grinder and two low-cost piezoelectric diaphragms were attached to each workpiece to guarantee redundancy. Roughness R a was also monitored to check existence of correlation with the EMI signals and relevant discussions regarding monitoring by EMI are presented. Results showed a great correlation between EMI measurement and surface roughness: 0.94 and 0.80 for both diaphragms. Since these diaphragms cost less than 1 US dollar and good correlation was verified, this monitoring system is promising to replace the traditional ones.
Keywords: Electromechanical Impedance; Piezoelectric transducers; Plunge cylindrical grinding; Structural health monitoring; Surface roughness